ANXIETY IN COLLEGE MAJOR DECISION MAKING AMONG ADOLESCENTS: GAMBARAN KECEMASAN DALAM PENGAMBILAN KEPUTUSAN JURUSAN KULIAH PADA REMAJA - Ananda, Yelsi Yuana; Hestyana Sari, Tesha; Annis Nauli, Fathra (Journal of Health and Cardiovascular Nursing, 2025)
Adolescence is a crucial stage of psychosocial development during which many high school students experience anxiety when choosing a college major, potentially affecting their psychological well-being and decision-making abilities. This study aimed to describe the level of anxiety among adolescents in making college major decisions and to identify the influencing factors. A descriptive quantitative study with a cross-sectional design was conducted among 77 twelfth-grade students at SMAN 1 Pekanbaru, selected through purposive sampling. Data were collected using a 20-item questionnaire covering aspects of talent, self-potential, department information, and counseling guidance. The validity of the instrument was tested using item–total correlation (r = 0.41–0.72), and its reliability was confirmed with Cronbach’s Alpha (? = 0.86). Univariate analysis revealed that 50.6% of respondents experienced anxiety in choosing their college major, with higher levels observed among females (35.1%) compared to males (15.6%), and a greater prevalence among first-born students (22.1%). Counseling guidance (77.9%) was identified as the most influential factor, followed by department information (58.4%) and talent/self-potential (6.5%). These findings indicate a relatively high prevalence of anxiety among adolescents in making college major decisions and emphasize the importance of school counseling, adequate access to information, and family support in helping students make appropriate educational choices.